Transparency of data on the value chain of medicines in Argentina, Brazil, and Colombia - Ribeiro, Alane Andrelino; Acosta, Angela; Pontes, Marcela Amaral; Machado Beltran, Manuel Alejandro; Peixoto, Rafaela Tavares; Leite, Silvana Nair (Frontiers in Pharmacology, 2023)
Introduction: The transparency of data on the value chain of medicines is crucial for the study and monitoring of the pharmaceutical system. These data may impact medicine pricing negotiations, contribute to patient access to pharmaceutical products, and strengthen health systems. Objective: This study analyzed the national strategies to ensure the transparency of data from medicine cost development to marketing in Argentina, Brazil, and Colombia. Method: A descriptive study was carried out by searching databases, reports, documents, and scientific articles published between January and August 2022 related to rules on transparency and databases, including 1) marketing authorization; 2) pricing; 3) intellectual property; 4) clinical trials; 5) research and development (R&D); and 6) health technology assessment (HTA) of selected biopharmaceuticals. Results: Transparency data, rules, and information are not uniform. The infostructures (organizational capacity for collecting and distributing information) regarding the pharmaceutical value chain in these three countries face limitations in appropriate measures to publicly share data and evidence, including pre-clinical data, clinical data, and costs. None of the countries require transparency about data on research and development costs. All three countries present similar publicization of data on marketing authorization and intellectual property, with some differences. The significant limitations in Argentina include the absence of formal price regulation and data on the volume of medicine purchased and respective amounts paid. Among the three countries, Brazil showed a higher degree of information transparency, perhaps due to the legal regulation that guarantees citizens access to information of public interest. Brazil also stands out in terms of the public availability of HTA reports and pricing, in addition to the highest volume of information. In contrast, Colombia has in place a decree that allows 5 years of trial data exclusivity for new medicines, an act contrary to data transparency. Despite the different stages of transparency, no country has evidenced a robust use of these data in public policy decision-making. Conclusion: The results reinforce the presence of information asymmetry between stakeholders, data fragmentation, data gaps and overlap, and difficulty in comparing available data across the three countries and the use of these data nationally to produce evidence.